Leadership and administrative management of the directors of the National University of Callao, Peru - Rojas Salazar, Arcelia Olga (2024)
Objective: Relate the leadership and administrative management of the directors of the operational areas in the National University of Callao (Peru), to 2022. Materials and methods: The study was of approach quantitative, descriptive, and applied in nature, and had a non-experimental, correlational, prospective, and cross-sectional design. The sample consisted of 56 directors from the various functional units of the university. It was used instrument used was a questionnaire to measure the variable leadership, with 24 items, as well as the variable administrative management, with 24 items, using the Likert scale (always, sometimes, and never). Results: It was found that there is a significant correlation between administrative management and leadership, which are highly correlated (rs = 0.816; p = 0.000 < 0.05); as well as the variables teamwork and planning in administrative management are moderately correlated (rs = 0.463, p = 0.000 < 0.05); the variables organization and execution in administrative management are highly correlated (rs = 0.738, p = 0.000 < 0.05) and the variables decision making and evaluation of results in administrative management are moderately correlated (rs = 0.654, p = 0.000 < 0.05). Conclusions: Leadership has a significant relationship with administrative management at the institutional level.